2017
DOI: 10.18203/2349-2902.isj20175152
|View full text |Cite
|
Sign up to set email alerts
|

Control of cystic artery during laparoscopic cholecystectomy: clips versus ultrasonic energy devices which is better?

Abstract: Background: This study was undertaken to know whether clip usage or ultrasonic energy application, obtains better haemostasis of cystic artery during laparoscopic cholecystectomy.Methods: About 80 patients undergoing laparoscopic cholecystectomy were selected on a prospective basis and divided into two equal groups- A and B. a comparative study was done between the two group. Clips were used to control cystic artery in group A patients and ultrasonic energy device was used for the same in group B.Results: In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
4
0
0
Order By: Relevance
“…Regarding gender distribution, our study observed a higher number of females compared to males in both the Monopolar (50 females, 20 males) and Harmonic groups (62 females, 15 males), with a p-value greater than 0.05. This finding aligns with the results reported by Venkatapuram and Sateesh [18] . Similarly, no statistically significant difference was found in the mean age of patients between the two groups, as supported by Venkatapuram and Sateesh [18] .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding gender distribution, our study observed a higher number of females compared to males in both the Monopolar (50 females, 20 males) and Harmonic groups (62 females, 15 males), with a p-value greater than 0.05. This finding aligns with the results reported by Venkatapuram and Sateesh [18] . Similarly, no statistically significant difference was found in the mean age of patients between the two groups, as supported by Venkatapuram and Sateesh [18] .…”
Section: Discussionsupporting
confidence: 93%
“…This finding aligns with the results reported by Venkatapuram and Sateesh [18] . Similarly, no statistically significant difference was found in the mean age of patients between the two groups, as supported by Venkatapuram and Sateesh [18] . The operative time was also similar between the groups (p=0.82), with mean times of 52.20 ± 4.60 minutes in the Monopolar group and 52.31 ± 4.62 minutes in the Harmonic group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations